Likelihood of repeat abortion in a Swedish cohort according to the choice of post‐abortion contraception: a longitudinal study. (14th March 2016) - Kilander, Helena; Alehagen, Siw; Svedlund, Linnea; Westlund, Karin; Thor, Johan; Brynhildsen, Jan
Abstract: Introduction: Despite high access to contraceptive services, 42% of the women who seek an abortion in Sweden have a history of previous abortion(s). The reasons for this high repeat abortion rate remain obscure. The objective of this study was to study the choice of contraceptive method after abortion and related odds of repeat abortions within 3–4 years. Material and methods: This is a retrospective cohort study based on a medical record review at three hospitals in Sweden. We included 987 women who had an abortion during 2009. We reviewed medical records from the date of the index abortion until the end of 2012 to establish the choice of contraception following the index abortion and the occurrence of repeat abortions. We calculated odds ratios (OR) with 95% CI. Results: While 46% of the women chose oral contraceptives, 34% chose long‐acting reversible contraceptives (LARC). LARC was chosen more commonly by women with a previous pregnancy, childbirth and/or abortion. During the follow‐up period, 24% of the study population requested one or more repeat abortion(s). Choosing LARC at the time of the index abortion was associated with fewer repeat abortions compared with choosing oral contraceptives (13% vs. 26%, OR 0.36; 95% CI 0.24–0.52). Subdermal implant was as effective as intrauterine device in preventing repeat abortions beyond 3 years. Conclusions: Choosing LARC was associated with fewer repeat abortions over more than 3 years of follow up.